Experimental and modelinginvestigation of the performance characteristics on diesel HCCI with hydrogen additive- a review - Supeni, Eris Elianddy; Yusaf, Talal F.; Wandel, Andrew P.; Buttsworth, David Robert; Mat Noor, Muhamad (Faculty of Mechanical Engineering, Universiti Malaysia Pahang, 2010)
Homogeneous charge compression ignition (HCCI) combustion has been attracting considerable attention due to higher efficiency with lower nitrogen oxide (NOx) and particulate matter (PM) emissions. The combustion process in dual fuel systems in HCCI engines is very complex due to the interactions of mixing and chemistry inside the combustion chamber during the late stages of the compression stroke and the ignition process. The ignition process is very critical with significant heat release from chemical reactions occurs and the timing is difficult to predict. Controlling auto ignition was considered as the significant problem to HCCI especially in tackling the sudden pressure rise in-cylinder. Thus, it will affect the performance and emission that varies with the operating engine condition and fuel properties. The sudden pressure is due to heterogeneous which result in flame propagation. This paper mainly reviews on dual fuels in internal combustion engine, with a particular focus on using hydrogen as a fuel additive.